Sumablay sa pagsablay a study on the lived experiences of UP Visayas Tacloban College extended students. - Ador, Helena May A.; Alegre, April Hannah E.; Tonolete, Karla Joy N. (Tacloban City Helena May A. Ador, April Hannah E. Alegre, and Karla Joy N. Tonolete, 2019)
The study explored the lived experiences and psychological well-being of delayed to graduate students of the University of the Philippines Visayas Tacloban College. The research has sought to answer the questions: (1) What experiences of UP undergraduate students leads to their delay to degree? (2) How does not being able to graduate on time affect their psychological well-being? and (3) What strategies do extended students utilize to overcome struggles of not being able to graduate on time?
To answer the research questions, the researchers utilized a qualitative study using phenomenological approach. A semi-structured interview was conducted individually to seven (7) extended students of the University of the Philippines Visayas Tacloban College. Also, thematic analysis was utilized to analyzed the patterns of meanings from the data gathered. The findings of this study showed that the factors they perceive as reasons as to why they were not able to graduate on time can be attributed to internal and external factors. Such examples of internal factors are lackluster behavior, personality and attitude, and own faulty decisions. Thus, external factors include lack of orientation from the university office regarding shifting to another degree program. Moreover, not being able to graduate on time affected the students' well-being in a sense that it dampens their self-esteem and decrease in perceived self-efficacy. Lastly, the study revealed that despite the challenges of extending, the participants still found ways to deal with these. Their coping strategies were categorized based on Weiten's four (4) types of coping mechanisms; (1) appraisal-focused, (2) problem-focused, (3) emotion-focused, and (4) meaning-focused.
Undergraduate thesis (B.A. Psychology) -- University of the Philippines, Tacloban.